Characteristics of patients with burn injuries managed at a tertiary care centre - Suntharamoorthy Iyer Thuraisamy Sarma; Sreekanthan Gobishangar; Suwaminathan Thiruvarangan; Nadarajah Hamsavakini; Paramanathan Shathana (Elsevier, 2024)
Introduction: Burn injuries are becoming a growing burden, negatively impacting both individuals and society. They affect a person's health and lead to psychosocial and economic problems. This study evaluates the prevalence, characteristics, and short-term outcomes of patients with burn injuries admitted to a tertiary care hospital in Northern Sri Lanka. Methods: This prospective cross-sectional study was conducted on patients with burn injuries admitted to Tertiary care centre Jaffna over six months in 2023. Ethical clearance was obtained from the Ethics Review Committee of the Faculty of Medicine, University of Jaffna. Baseline characteristics and clinical features during hospitalisation were recorded. Categorical variables were compared using the Chi-square test, with post hoc Tukey tests conducted where applicable. Results: This study included 57 patients aged 1 to 88 years, with a mean age of 35.19 ± 21.16 years. Most participants were female (53.4 %), and most had completed secondary education (62.1 %). Approximately 65.5 % were employed in unskilled jobs, with the remainder in skilled professions. Accidental burns were the most common cause (72.4 %), with 84.5 % of injuries occurring at home, though suicide-related burns accounted for 24.1 %. Flame-related burns constituted 50 % of injuries, with first-degree burns being the most common (44.8 %). The availability of first aid significantly influenced outcomes, with 74.1 % receiving assistance, primarily through removing clothing (43.8 %) and using running water (15.8 %). A combined approach of care was received by most patients (52.7 %), while 8.8 % were hospitalised in the plastic and reconstructive surgery department. Many patients had burns covering less than 10 % of their body surface area (46.6 %). Conclusion: The findings of this study on patients with burn injuries underscore the importance of understanding the causes of burns, administering appropriate first aid, recognising different injury types and severities, assessing the total burn surface area, and tailoring patient treatment. These insights are crucial for informing prevention strategies and healthcare planning, aiming to mitigate the impact of burn injuries and improve patient outcomes.